Comparison of titrated oral misoprostol solution versus vaginal misoprostol for induction of labour in term obstetric patients for obstetric and neonatal outcomes: a randomized controlled trial - Mahajan, Puneeta; Shitole, Rajendra Popatrao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: With more than 15% of all gravid women requiring prostaglandins in cervical ripening and labour induction. However, evidence is not clear about the preferred route or dose of the drug. So this study was designed with objectives to compare the induction delivery interval and safety of titrated oral misoprostol solution with vaginal misoprostol for labour induction in term primigravida women. Methods: In this randomised controlled trial out of 576 eligible women, 220 women as per inclusion criteria between 37 and 42 weeks of gestation with an unfavourable cervix (Bishop score <6) with indication for labour induction were randomly assigned (110each) to receive titrated oral solution of 20 mL misoprostol solution (1 mcg/mL) every 1 hour for four doses and then were titrated against individual uterine response or vaginal misoprostol 25 mcg every 4 hours. Vaginal delivery within 12 hours was the primary outcome. The data were analyzed by intention-to-treat. Results: Vaginal delivery occurred within 12 hours in 56 (50.9%) women in the titrated oral group and 24 (21.8%) women in the vaginal group with significant p-value (<0.001). The incidence of caesarean, hyper stimulation, low apgar score was less in the titrated oral group. More women experienced nausea in the titrated oral group. Conclusions:Titrated oral misoprostol is safe and effective for labour induction in primigravida patients with unfavourable cervix.